Kesalahan Ucapan dalam Pidato Pelantikan Donald Trump pada Tahun 2025: Analisis Psikolinguistik - Pasaribu, Lolita Amelia; Lasut, Theresia Maria Conny; Lotulung, Donald Ringgo (Linguistika Kultura, 2026)
Speech errors emerge when linguistic planning at the conceptualization stage fails, resulting in unintended distortions of sound, form, or meaning. The objectives of this research are to identify the types of slips of the tongue, to classify them, and to analyze the factors contributing to their occurrence in the 2025 inauguration speech of Donald Trump. This study employed a descriptive-qualitative methodology, guided by the theoretical frameworks of Fromkin (1973) and Freud (1901). Data collection involved identifying types of the slip in video recordings of Trump’s inauguration speech accessible via the ABC News YouTube channel. This focused with the examination of eight slip types: anticipation, preservation, substitution, blends, additions, deletions, sound exchanges, and morpheme exchanges. The findings reveal that there are six of types of slips of the tongue occurred in Trump’s speech: perseveration (three occurrences), anticipation (two occurrences), substitution (two occurrences), blend (one occurrence), deletion (one occurrence), and addition (five occurrences). Notably, sound exchanges and morpheme exchanges were absent. Addition emerged as the most frequent error type, while blend and deletion were the least frequent. This research significantly advances the understanding of speech errors in high-stakes political communication. It demonstrated that slips of the tongue reflect cognitive load, psychological pressures, and contextual demands inherent to public speaking.